Implementation of the Family Hope Program (PKH) in Poverty Alleviation in the Assilulu Community, Leihitu District, Central Maluku Regency - Mahulette, Angriany; Osok, Rafael Marthinus; Leuwol, Ferdinand Salomo (Jurnal Pendidikan Geografi Unpatti, 2022)
The Hope Family Program (PKH) itself is a social protection program that provides non-cash assistance to the Poor Family designated as the Beneficiary Family. This research was conducted in Assilulu District Leihitu District Central Maluku Regency. In June 2022, through the method of collecting data used including observation, interviews and documentation. The results of the study show that PKH has been in Assilulu Country since 2016 but that year has not been fully realized until 2020. This PKH program has given waivers in this regard education, including elementary, junior high and high school. For health bags of pregnant women/nifas or toddlers and social well-being, for severe disability. In addition, it is also in the form of cash and non-conditional aid for poor families. While the factor of inhibitory factors is still the number of people who have not received good help